1991
DOI: 10.1111/j.1348-0421.1991.tb01571.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Clumping and Fibrinogen‐Binding Activities of Staphylococcus aureus at Various Growth Stages

Abstract: Clumping and fibrinogen-binding activities of 4 Staphylococcus aureus strains (Cowan I, Newman D2C, Wood 46 and NCTC 5655) were assayed with a semiquantitative clumping test and an enzyme-linked immunosorbent assay (ELISA), respectively.Distinct positive clumping was detected with whole cells of the 3 strains except Wood 46. Amounts of fibrinogen required for a definite clumping depended greatly on strains as well as on their growth phases.On the other hand, fibrinogen-binding activities were detected both in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…Interestingly, only one strain, Wood 46, did not show strong aggregation. Because that strain does not adhere to fibrinogen or fibronectin [20,21], these results are in good accordance with our findings described below, attributing a key contribution of fibrinogenand fibronectinbinding proteins to aggregation in SF. Light (Figure 2D and 2E) and electron microscopic (Figure 2F ) examination verified the extreme clumping behavior of S. aureus USA300 grown in SF.…”
Section: Formation Of S Aureus Aggregates In Sfsupporting
confidence: 92%
“…Interestingly, only one strain, Wood 46, did not show strong aggregation. Because that strain does not adhere to fibrinogen or fibronectin [20,21], these results are in good accordance with our findings described below, attributing a key contribution of fibrinogenand fibronectinbinding proteins to aggregation in SF. Light (Figure 2D and 2E) and electron microscopic (Figure 2F ) examination verified the extreme clumping behavior of S. aureus USA300 grown in SF.…”
Section: Formation Of S Aureus Aggregates In Sfsupporting
confidence: 92%
“…The wild type S. aureus that we used in this study was Newman D2C, which has been reported as a new reference strain for SrtA studies ( Miller et al, 1977 ) due to its being coagulase-negative ( Yonemasu et al, 1987 , 1991 ) and non-hemolytic ( Chen et al, 2013 ). To our current knowledge, SrtA is the most important virulence factor in this strain, and therefore this strain has an advantage for studying the function of SrtA and the activity of SrtA inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…To address this question, we chose S. aureus Newman D2C as a new reference strain for SrtA studies (Miller et al ., ). Because this strain is coagulase‐negative (Yonemasu et al ., , ), we could exclude the effects of coagulase and focus just on the functions of SrtA. Here, we investigated the roles of SrtA in the pathogenesis of S. aureus ‐induced mastitis.…”
Section: Introductionmentioning
confidence: 99%